Design And Prototyping Of Arduino Microcontroller-Based Vacuum Sucking Tools - Alexius Ulan Bani; Fifto Nugroho; Jefon Krisna Parell Marunduri (Yayasan Bina Internusa Mabarindo, 2022)
Cleanliness is a very important factor for human life. Good hygiene will reflect a healthy lifestyle. Dust is one of the factors that affect the cleanliness of a room. a lot of dust and scattered on the floor will make the room dirty. In this study, an automatic vacuum cleaner will be designed to clean dust on the floor in a room. In designing and making prototypes of this Arduino microcontroller-based vacuum cleaner, it was designed in terms of hardware and software.The test results of the vacuum cleaner run well and properly, but the dust suction is not strong enough so that it is not optimal for sucking large or heavy dust.